SIADH in COVID 19 infection, an association or cause : A case report - Shamarukh, Karishma; Rahman, Sharmin; Chy, Umme Kulsum; Sultana, Amina; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2020)
One of the leading cause of hyponatremia is syndrome of inappropriate antidiuretic hormone secretion (SIADH). Various etiologies of hyponatraemia have been observed till today but its association with Covid leading to SIADH is rare. Therefore, we present a case where SIADH was associated with Covid-19 pneumonia. This was a case of a 66 years old male with multiple co-morbidities presenting with symptoms of Covid infection including generalized weakness. After confirming Covid 19 infection management was started accordingly but patient’s weakness seemed to increase. He was found to have low sodium level of 105 mmol /L and investigations confirmed that he was having SIADH. He was treated with hypertonic saline, fluid restriction and his symptoms and laboratory parameters gradually improved. Bangladesh Crit Care J September 2020; 8(2): 126-128